PENGARUH CONTENT MARKETING, FREKUENSI PENAYANGAN IKLAN, DAN KUALITAS PELAYANAN DALAM SOSIAL MEDIA (INSTAGRAM) TERHADAP IMPULSE BUYING (STUDI KASUS PADA TOKO FASHION QOMESHOP KOTA KEDIRI) - Nurul Lailiawati , Nurul (Universitas Nusantara PGRI Kediri, 2022)
Technology currently controls people's lives, and if used properly, it may give numerous advantages. Especially in light of the COVID-19 pandemic, the majority of purchasing and selling transactions are conducted digitally. Through social media, marketing becomes more effective and efficient, creating several options for retailers to attract more impulse buyers through digital incentives. This study aims to determine if the variables of content marketing, frequency of ad serving, and service quality have a significant impact on impulse purchases at the Qomeshop Fashion Store in Kediri City. Using questionnaires as study data, a quantitative method is employed. This study employs the technique of accidental sampling, and the sample consists of forty consumers who entered the qomeshop fashion store in Kediri. The SPSS IBM 23 application is utilized to perform the data analysis. This study used multiple linear regression, the coefficient of determination (R2), the t-test, and the F-test for data analysis. The results of this study reveal that content marketing, ad serving frequency, and service quality have a substantial impact on impulse purchases. At the Qomeshop Fashion Store in Kediri, content marketing, ad serving frequency, and service quality all have a substantial influence on impulse purchases.